Parent-adolescent relationship and adolescent internet addiction: A moderated mediation model. (September 2018) - Wang, Wei; Li, Dongping; Li, Xian; Wang, Yanhui; Sun, Wenqiang; Zhao, Liyan; Qiu, Lilan
Abstract: Substantial research has found that positive parent-adolescent relationship is associated with low levels of adolescent Internet addiction (IA). However, little is known about the mediating and moderating mechanisms underlying this relation. The present study examined a moderated mediation model that included the parent-adolescent relationship (predictor variable), emotion regulation ability (mediator), stressful life events (moderator), and IA (outcome variable) simultaneously. A total of 998 ( M age = 15.15 years, SD = 1.57) Chinese adolescents completed the Parent-Adolescent Relationship Scale, Emotion Regulation Ability Scale, Adolescent Stressful Life Events Scale, and Internet Addiction Diagnostic Questionnaire. After controlling for adolescent gender, age, and family socioeconomic status, results revealed that good parent-adolescent relationship was positively associated with adolescent emotion regulation ability, which in turn was negatively associated with their IA. Moreover, stressful life events moderated the second part of the mediation process. In accordance with the reverse stress-buffering model, the relation between emotion regulation ability and adolescent IA was stronger for adolescents who experienced lower levels of stressful life events. The findings and their implications are discussed and a resilient contextual perspective proposed. Highlights: A good parent-adolescent relationship (PAR) negatively predicted Internet addiction (IA). Emotion regulation (ER) partially mediated the relation between PAR and IA. The impact of ER on IA was stronger for those with fewer stressful life events.